Just like Jesus - Lucado, Max. (Nashville, TN : Word Pub., 1998)
In recounting the biblical stories of Jesus' life and deeds, Lucado then explains how Jesus' acts of compassion, forgiveness, honesty, and faith can be reflected in anyone's everyday life. Lucado's concrete analogy of "just like Jesus" helps many readers grasp the fundamentals of Christianity in a new and inspiring way.
A heart Like His -- Loving the People You Are Stuck With: A Forgiving heart -- The Touch of God: A Compassionate Heart -- Hearing God's Music: A Listening Heart -- Being Led by an Unseen Hand: A God-Intoxicated Heart -- A Changed Face and a Set of Wings: A Worship-Hungry Heart -- Golf Games and Celery Sticks: A Focused Heart -- Nothing but the Truth: An Honest Heart -- The Greenhouse of the Mind: A Pure Heart -- Finding Gold in the Garbage: A Hope-Filled Heart -- When Heaven Celebrates: A Rejoicing Heart -- Finishing Strong: An Enduring Heart -- Conclusion: Fixing Your Eyes on Jesus.
Includes study guide: p. [170]-223.
Includes bibliographical references.
Keywords: Jesus Christ -- Example; Spiritual life -- Christianity; Jesus Christ; Jesus Christ as an example to be followed; Spiritual life -- Christianity